Farmer awareness of cow longevity and implications for decision-making at farm level. (2nd January 2016) - Bergeå, Hanna; Roth, Anki; Emanuelson, Ulf; Agenäs, Sigrid
ABSTRACT: The aim of this study was to investigate if farmer awareness of longevity can explain why the longevity of dairy cows does not increase in Sweden, despite the fact that the genetic trend for longevity in Swedish dairy cattle is positive. In this study, farmers' decisions were put in the forefront through a qualitative study with semi-structured interviews. The results showed that farmers seemed well aware of biological factors related to cow longevity, that they think the demands on dairy cows have increased over time and that they correlate the higher demands to shorter longevity. However, the farmers had not worked explicitly with longevity of their own herd. There are subjective management decisions behind a culling of a dairy cow, and the reporting of culling reasons does not mirror the farmer's reasoning behind the decisions, which is a key factor determining longevity.